Architectural Transformations and Planning Regulation Violations in Residential Housing Allotments: A GIS Approach in Zouaghi Slimane-Ain El Bey, Phase 2, Constantine (Algeria) - Yasser Nassim, Benzagouta (International Journal of Computational and Experimental Science and Engineering, 2026)
This paper investigates residential housing allotments in the city of Constantine, Algeria, with a particular focus on their compliance with urban planning regulations. The study adopts the urban residential area of Zouaghi Slimane, Ain El Bey, Phase 2, as a representative case study, as this subdivision is characterized by a high prevalence of urban planning violations committed by residents. The research aims to identify and analyze the various forms of urban violations, explore their underlying causes, and ultimately propose a set of recommendations to mitigate and limit the spread of such practices. Geographic Information Systems (GIS) are employed as the primary analytical tool, enabling the spatial identification, quantification, and visualization of violations. The findings highlight the effectiveness of GIS as a decision-support tool for urban control, monitoring, and sustainable urban management